Participatory rural appraisal principles, methods and application - Narayanasamy, N.; Sage eBooks (Delhi ; London : SAGE, 2008)
Provides a comprehensive and analytical picture of the evolution and principles of PRA/PLA, with a number of illustrations and field-based studies. The author looks at the essential features of each method and highlights their applications in areas such as participatory poverty assessment and assessment of hunger.
Specialized.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Participatory rural appraisal; Electronic books